2022
DOI: 10.1186/s41077-022-00233-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternating between active and passive facilitator roles in simulated scenarios: a qualitative study of nursing students’ perceptions

Abstract: Background High-fidelity simulation refers to realistic interactivity between students and an advanced simulator. During simulated scenarios, the facilitator often needs to provide guidance to the active students to bridge the gap between their insufficient practical nursing skills and clinical learning needs. Facilitators’ guidance should support students in problem-solving and help them progress in their simulation experiences. The aim of this study was to explore and describe nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the effectiveness of debriefing can vary depending on the skill and experience of the facilitator, highlighting the need for comprehensive training (Guerrero, Ali, & Attallah, 2022; Guerrero, Tungpalan‐Castro, & Pingue‐Raguini, 2022). Facilitating SBL requires diverse skills, including relational, pedagogical, emotional, clinical, technical and SBL abilities (Solli et al., 2022). Facilitators must be able to adjust cues individually to accommodate different learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of debriefing can vary depending on the skill and experience of the facilitator, highlighting the need for comprehensive training (Guerrero, Ali, & Attallah, 2022; Guerrero, Tungpalan‐Castro, & Pingue‐Raguini, 2022). Facilitating SBL requires diverse skills, including relational, pedagogical, emotional, clinical, technical and SBL abilities (Solli et al., 2022). Facilitators must be able to adjust cues individually to accommodate different learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…As the facilitators’ learning support abilities play an important role in simulation education [ 17 ], it is important to standardize the facilitators’ learning support abilities. Facilitators must appropriately understand the needs of the learners and respond flexibly [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the simulations provided opportunities for students to engage in discussions and receive feedback from instructors and observers for improving both clinical and non-technical skills. Similarly, Solli et al (2022) suggested that it is essential to create a trusted learning environment for students with dynamic interaction and collaboration. Such an environment would contribute to fostering a learner-centered perspective.…”
Section: Discussionmentioning
confidence: 99%